To examine the potential effectiveness of Psidium guajava in Letrozole induced polycystic ovarian syndrome in female albino rats (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Polycystic ovarian syndrome (PCOS) is a common endocrine disorder characterized by hormonal imbalances, metabolic disturbances, and ovarian dysfunction. This study aimed to investigate the therapeutic potential of methanol extract from Psidium guajava leaves as a natural remedy for alleviating PCOS symptoms in female albino rats. The experimental approach involved assessing critical physiological and biochemical markers both before and after treatment, including body weight, blood levels of testosterone, luteinizing hormone (LH), and follicle-stimulating hormone (FSH), ovarian weight, and the FSH/LH ratio. Anti-inflammatory effects were evaluated by measuring inflammatory markers like TNF-α and lipid-derived mediators. Furthermore, a histological analysis of ovarian tissue was performed to observe changes in follicular development and ovarian structure. The results showed that Psidium guajava treatment significantly improved hormonal profiles, reduced inflammation markers, and promoted the regeneration and maturation of ovarian follicles, counteracting hyperandrogenism and inflammation associated with PCOS. These findings suggest that Psidium guajava leaf extract could be a promising adjunct therapy for managing PCOS, supporting endocrine balance, ovarian health, and inflammation reduction. However, further studies are needed to understand the underlying mechanisms and long-term effects of this botanical treatment.